Crude palm stearin influences the performance, carcass quality and intestinal morphology of broiler chicks - Khaskheli, A. A.; Chou, L. (Diponegoro University, 2021)
The main objective of the investigation was to observe the growth performance, carcass yield, meat quality, and intestinal morphology of broiler chicks with respect to the dietary crude palm stearin (CPS). The study was conducted on 200 birds and dividing them into two experimental groups viz control and CPS treated group with 10 replications of 10 birds in each. Chicks under the control group were fed basal diet only, however in CPS treated group chicks were fed the basal diet supplemented with 3% CPS. Birds were reared for 42 days and data regarding different parameters of study was recorded. Data were analyzed by student T-test and differences were considered significant at P < 0.05.Results indicated CPS treated group pertaining to lower final body weight, daily weight gain, feed conversion ratio, feed intake, dressing percentage, fillets, thight+drumsticks, and wings percentages. CPS treated group possessed lower liver, spleen, gizzard, and abdominal fat weights. Breast meat holds lower values for shear force, drip loss in CPS treated group, while cooking loss found vice versa. Abdominal fat breast in the meat and thigh skin possessed higher a* (redness) and b* (yellowness) values in CPS treated chicks, while breast skin and thigh meat hold lower a* and b* values in CPS treated chicks compared to control. Intestinal villus height, villus area and crypts depth in duodenum found considerably higher in the CPS treated chicks. Jejunum in CPS treated group possessed higher crypt depth but villus height and villus area remained lower. In conclusion, CPS impairs overall growth performance, carcass yield and meat quality but supports the intestinal morphology.